A good day at work. But what really is a good day at work?. Issue 1 (23rd July 2018) - Jones, Alex
Abstract : Social pedagogy encourages practitioners to view everyday situations as potential learning opportunities for young people and to support them to learn through doing rather than being told. This article uses a reflective account from an experienced residential care practitioner to illustrate how creating a space in sports activities for young people to learn together and support each other to solve problems can provide an opportunity for young people to develop valuable interpersonal skills and relationships with each other.